Extravagant abjection blackness, power, and sexuality in the African American literary imagination - Scott, Darieck (New York New York University Press, 2010)
Summary: Challenging the conception of empowerment associated with the Black Power Movement and its political and intellectual legacies, this title contends that power can be found not only in martial resistance, but, surprisingly, where the black body has been inflicted with harm or humiliation.
Introduction: Blackness, abjection, and sexuality -- Fanon?s muscles: (Black) power revisited -- "A race that could be so dealt with" : terror, time, and (Black) power -- Slavery, rape, and the Black male abject -- Notes on Black (power) bottoms -- The occupied territory : homosexuality and history in Amiri Baraka?s Black arts -- Porn and the n-word : lust, Samuel Delany?s The mad man, and a derangement of body and sense(s) -- Conclusion: Extravagant abjection.
Keywords: American fiction -- African American authors -- History and criticism; African American men in literature; Power (Social sciences) in literature; Race relations in literature; Rape in literature; Homosexuality in literature; Pornography in literature; Abjection in literature